2019
DOI: 10.1242/jcs.229526
|View full text |Cite
|
Sign up to set email alerts
|

The route of the visual receptor rhodopsin along the cilium

Abstract: The photoreceptor outer segment is the most elaborate primary cilium, containing large amounts of rhodopsin (RHO) in disk membranes that grow from a connecting cilium. The movement of RHO along the connecting cilium precedes formation of the disk membranes. However, the route that RHO takes has not been clearly determined; some reports suggest that it follows an intracellular, vesicular route along the axoneme, possibly as an adaptation for the high load of delivery or the morphogenesis of the disk endomembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…While the outer segment of photoreceptors is tightly packed with membranes and proteins necessary to phototransduction, the inner segment acts as biosynthetic factory to produce needed proteins and fatty acids. The continuous flow of these fundamental factors to the outer segments relies on a highly specialized connecting cilium (Besharse et al, 1977; Wolfrum and Schmitt, 2000; Burgoyne et al, 2015; Chadha et al, 2019) and it is not surprising that almost one quarter of known photoreceptor degeneration-causing genes are involved in the function of this organelle (RetNet, the Retinal Information Network) 1 . The Retinitis Pigmentosa GTPase Regulator (RPGR) is located on the X chromosome and, together with its interactome (Zhang et al, 2019), plays a critical role for connecting cilium function (Megaw et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the outer segment of photoreceptors is tightly packed with membranes and proteins necessary to phototransduction, the inner segment acts as biosynthetic factory to produce needed proteins and fatty acids. The continuous flow of these fundamental factors to the outer segments relies on a highly specialized connecting cilium (Besharse et al, 1977; Wolfrum and Schmitt, 2000; Burgoyne et al, 2015; Chadha et al, 2019) and it is not surprising that almost one quarter of known photoreceptor degeneration-causing genes are involved in the function of this organelle (RetNet, the Retinal Information Network) 1 . The Retinitis Pigmentosa GTPase Regulator (RPGR) is located on the X chromosome and, together with its interactome (Zhang et al, 2019), plays a critical role for connecting cilium function (Megaw et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessity of an accessory protein like MRAP2 for ciliary trafficking of specific GPCRs was not considered, suggesting that these screens may have missed a number of ciliary GPCRs, including MC4R 41,42 . Whether other ciliary GPCRs use accessory proteins for ciliary trafficking is an open question, but is hinted at by studies demonstrating that proteins, such as Rhodopsin, localize robustly to cilia in their native cell types, but less well in heterologous ciliated cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the CTS within the IC3 loop of SSTR3 provides strong binding to a recombinant BBSome core complex, but that the IC3 loop of 5-HT-6 receptor, which is similar to that of rhodopsin, provided only weak interaction (Klink et al, 2017 ). This weak interaction, as well as the presence of an FR motif in rhodopsin helix 8, which also has weak affinity to the BBSome (Klink et al, 2017 ; Yang et al, 2020 ), may support the low presence of rhodopsin in primary cilia (Trivedi and Williams, 2010 ; Trivedi et al, 2012 ; Wang et al, 2012 ; Geneva et al, 2017 ; Chadha et al, 2019 ).…”
Section: The Bbsome In Photoreceptorsmentioning
confidence: 99%
“…Moreover, recent careful EM studies have clearly shown nascent discs to be open to the extracellular milieux (Burgoyne et al, 2015 ; Ding et al, 2015 ; Volland et al, 2015 ). Finally, immunogold labeling experiments have shown rhodopsin to be located in the ciliary membrane of mouse photoreceptors with little in the lumen of the cilium (Wolfrum and Schmitt, 2000 ; Burgoyne et al, 2015 ; Chadha et al, 2019 ).…”
Section: Intrinsic Membrane Protein Compartmentalization Within the Cmentioning
confidence: 99%